Strategi Pengembangan Usaha dalam Meningkatkan Penjualan pada Kopi Bubuk Raosan di Desa Tribudisyukur Kabupaten Lampung Barat - Nofa Pratama Saputra; Melan Susanty Purnamasari; Suhartina (Business Perspective Journal, 2026)
Coffee plants continue to grow as a leading plantation commodity capable of supporting the national economy. This study aims to determine the business development strategies used to increase sales of Raosan ground coffee in Tribudisyukur Village, West Lampung Regency. This research uses a qualitative method. The key informants and informants in this study include the owner of the Raosan Ground Coffee business, the employees, and the consumers. Data were collected through observation, interviews, and documentation. The data analysis techniques used were data reduction, data display, and conclusion drawing. The results of this study show that the development strategies applied by the Raosan Ground Coffee business-when viewed through indicators such as increased income, increased number of customers, improved product quality, and enhanced human resource (HR) capacity-indicate that the business has grown quite well. This is evident from the increase in sales compared to previous periods based on interview data. Although there are still several obstacles, such as limited equipment, financial constraints, and suboptimal social media promotion, the strategies implemented are considered effective in driving business growth. With its strong local potential, the Raosan Ground Coffee business has significant opportunities to expand further.   Keywords:  development strategy, ground coffee, increasing sales